The Influence of Service Quality Dimensions (Tangible, Emphaty, Responsiveness, Reliability, And Assurance) on Customer Satisfaction (A Study at the Depot Titik Koempoel Pandaan) - Ivar Gymnastiar; Siti Ning Farida (Malacca: Journal of Management and Business Development, 2026)
This study aims to analyze the influence of service quality dimensions, namely tangible, reliability, responsiveness, assurance, and empathy, on customer satisfaction at Depot Titik Koempoel Pandaan. The study employed a quantitative associative approach. The sample consisted of 100 respondents selected using accidental sampling techniques. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with SPSS software. The findings indicate that all dimensions of service quality simultaneously have a significant influence on customer satisfaction. Partially, reliability, responsiveness, and assurance have a positive and significant effect on customer satisfaction, while tangible and empathy do not show a significant effect. These results indicate that interaction-based service aspects are more influential than physical evidence in shaping customer satisfaction within the culinary business sector.